2022
DOI: 10.1039/d2cc03588j
|View full text |Cite|
|
Sign up to set email alerts
|

Traceless enzymatic synthesis of monodispersed hypermodified oligodeoxyribonucleotide polymers from RNA templates

Abstract: We have developed a new alternative for enzymatic synthesis of single-stranded hypermodified oligodeoxyribonucleotides displaying four different hydrophobic groups based on reverse transcription from RNA templates catalyzed by DNA polymerases using...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 42 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…However, such ssON isolation could be also performed using regular 5′-biotin modified templates, λ exonuclease digestion of 5′-phosphorylated templates, or our recently published method of traceless template and primer region RNase digestion. 68 The PEX products can also be used directly as double stranded ONs, which can be purified using the commercially available kits for short DNA fragment purification.…”
Section: Discussionmentioning
confidence: 99%
“…However, such ssON isolation could be also performed using regular 5′-biotin modified templates, λ exonuclease digestion of 5′-phosphorylated templates, or our recently published method of traceless template and primer region RNase digestion. 68 The PEX products can also be used directly as double stranded ONs, which can be purified using the commercially available kits for short DNA fragment purification.…”
Section: Discussionmentioning
confidence: 99%
“…However, such ssON isolation could be also performed by regular 5'-biotin modified templates,  exonuclease digestion of 5'-phosphorylated templates, or our recently published method of traceless template and primer region RNase digestion. 62 PEX products can be also used directly as double strand ON, which can be purified using the commercially available kits for short DNA fragments purification.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have demonstrated the incorporation of redox reporters onto both DNA and RNA oligonucleotides at the 3’ end [25,26] . Both fluorescence modified nucleotides and more hydrophobic ( 8 ) nucleotides have also been demonstrated as substrates for end labelling [27,28] . This ability to end label oligonucleotides has allowed researchers to impart additional functionality onto DNA through a simple and convenient method to allow for further applications of nucleic acids.…”
Section: Applications Of Tdt Enzymementioning
confidence: 99%
“…[25,26] Both fluorescence modified nucleotides and more hydrophobic (8) nucleotides have also been demon-strated as substrates for end labelling. [27,28] This ability to end label oligonucleotides has allowed researchers to impart additional functionality onto DNA through a simple and convenient method to allow for further applications of nucleic acids. For instance, in 2012 and 2015, Winz et al demonstrated the use of TdT in the end labelling of DNA and RNA with different click chemistries (7) to allow for further conjugation of different functional groups (biotin, fluorescent dyes etc) through copper catalysed reactions of azides with an alkynes.…”
Section: The Application Of Tdt In Molecular Biologymentioning
confidence: 99%